Economics and Mathematical Modeling in Health-Related Research - Weresa, Marzenna Anna; Ciecierski, Christina; Filus, Lidia (Brill, 2022)
The definition of a healthcare system evolves continuously, becoming broader and more complex with each rendering. Healthcare systems can consist of many different elements, including but not limited to: access to comprehensive medical care, health promotion, disease prevention, institutional framework, financing schemes, government responsibility over health, etc. In light of its broad classification of healthcare, this book focuses on a wide spectrum of health-related issues ranging from risk factors for disease to medical treatment and possible frameworks for healthcare systems. Aging populations, increasing costs of healthcare, advancing technology, and challenges created by the COVID-19 pandemic require an innovative conceptual and methodological framework. By combining the experience and effort of researchers from a variety of fields including mathematics, medicine and economics, this book offers an interdisciplinary approach to studying health-related issues. It contributes to the existing literature by integrating the perspective of treatment with the economic determinants of health care outcomes, such as population density, access to financial resources and institutional frameworks. It also provides new evidence regarding the pharmaceutical industry including innovation, international trade and company performance. Contributors are: Sayansk Da Silva, Joe Feinglass, Scott W. Hegerty, Joseph E. Hibdon, Jr, Arkadiusz Michał Kowalski, Małgorzata Stefania Lewandowska, Dawid Majcherek, Ewelina Nojszewska, Izabela Pruchnicka-Grabias, Agata Sielska and Julian Smółka.